“Diagnóstico del uso y manejo de fungicidas en la finca cacaotera La Providencia del Recinto Pretoria Cantón Montalvo” - Silva Sañay, Sergio Ernesto (2019)
SUMMARY The practical component was carried out in the Finca Cocoa La Providencia located in the precinct Pretoria Canton Montalvo Province of the rivers. Based on the survey conducted was able to show the situations detected: It was evident that the farm use fungicides of chemical origin in cocoa crops, stating that their action is more effective, so it is common to make use of fungicides as a method of disease control. Although they have the protective equipment 15% of the workers have shown poisoning because of the vapors that expel the fungicides. And when an intoxication occurs, the administration takes emergency measures; 67% go to the doctor, and 33% of the members do not take any responsible moderation. But farmers ' scarce knowledge or interest in taking the right steps to reclycle and drill containers after using their content, throw empty containers out in the open and reuse them with proper washing. However, 70% mention applying pesticide instructions. Key words: Cocoa, fungicides, pesticides, poisoning